Telegraph Avenue : a novel - Chabon, Michael (New York : Harper, 2012)
In this novel the author takes us to Telegraph Avenue. It is a story that explores the profoundly intertwined lives of two Oakland, California families, one black and one white. Here he creates a world grounded in pop culture: Kung Fu, 1970s Blaxploitation films, vinyl LPs, jazz and soul music, and an epic of friendship, race, and secret histories.
Keywords: Oakland (Calif.) -- Fiction; Berkeley (Calif.) -- Fiction; Domestic fiction